Chapter Introduction - Murphy, Neil; Wang, W. Michelle; Lee, Cheryl Julia (Taylor & Francis, 2024)
The Routledge Companion to Literature and Art explores the links between literature and visual art from classical ekphrasis through to contemporary experimental forms. The collection’s engagement with diverse literary and cultural artifacts offers a comprehensive survey of the vibrant interrelationships that currently inform literary studies and the arts. Featuring four sections, the first part provides an overview of theoretical approaches to art and literature from philosophy and aesthetics through to cognitive neuroscience. Part two examines one of the most important intersections between text and image: the workings of ekphrasis across poetry, fiction, drama, comics, life and travel writing, and architectural treatises. Parts three and four consider intermedial crossings from antiquity to the present. The contributors examine the rich intermedial experiments that range from manuscript studies to infographics in graphic narratives, illuminating the vibrant ways in which texts have intersected with illustration, music, dance, architecture, painting, photography, media installations, and television. Throughout this dynamic collection of 37 chapters, the contributors evolve existing critical debates in innovative new directions. The volume will be a critical resource for advanced undergraduate and graduate students, as well as specialist scholars working in literary studies, philosophy of art, text and image studies, and visual culture. The Introduction and Chapters 10, 14 and 37 of this book are freely available as a downloadable Open Access PDF at "http://www.taylorfrancis.com" http://www.taylorfrancis.com under a Creative Commons Attribution (CC-BY) 4.0 license.